Improving Students’ Reading Comprehension by Activating Their Schema (An Action Research on VIII Grade of SMP Madinatul Ulum Tembelang Jombang) - Iin Baroroh Maarif; Nurul Afidah (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2018)
This research aims to know the improvement of students' understanding on English text through the implementation of activating schema strategy. Activating schema strategy is one of teaching strategy that focuses on how students are able to understand and comprehend English text easily by connecting their prior knowledge. This research is Classroom Action Research. The object of the research is the 8th grade students at SMP Madinatul Ulum Tembelang Jombang. Number of students consists of 38 people. The data collecting were obtained from teacher observation, field note and student questionnaire. The results of this research indicate the average score of students in English subject prior to the implementation of activating schema strategy of 59.50 (in preliminary study), while the average score after the implementation of the strategy increased up to 71.42 in cycle 2. This indicates an increasing in student learning outcomes after the implementation of this strategy. Furthermore, most students are more motivated and enjoy in teaching learning process